Adolescent Perception and Attitude Toward Mental Disorders: A Survey Among Adolescents in an Urban Area in The Federal Capital Territory, Abuja - Idoko, Lucy O.; Okafor, Kingsley Chinedu; Ameerah, Adeyemi A (British Journal of Healthcare and Medical Research, 2023)
Background: Generally, there is limited public understanding of mental illness, and there are certain misconceptions regarding those who suffer from mental disorders. They cut across cultures, periods, and religions. Adolescents are not exempted from this limitation. This study seeks to assess the perception and attitude of adolescents towards mental disorders in Abuja. Methods: This was descriptive, cross-sectional study conducted between August and October, 2021 among adolescents in an Urban Area in the Federal Capital Territory, Abuja. Ethical approval was granted by Bingham University Teaching Hospital, Jos, Plateau State. Results: In summary, 239 (59.0%) were females, 166 (41.0%) were males. Adolescents had a negative attitude to mental illness as indicated by the composite mean (2.48). Only 55 (13.6%) believe that they are dangerous, 68 (16.5%) agree that they are aggressive and violent, 176 (43.5%) stated that they should be locked up. About half 229 (56.6%) stated that they would not be scared to be friends with a mentally ill person, 86 (21.3%) stated that will not. Over a third 280 (69.2%) of adolescents agreed to be in same class/school with a person that has a mental disorder, while 62 (15.4%) stated that they will not, 119 (29.4%) said that they would be embarrassed if they had a mental disorder, 145(35.8) said they cannot be friends with people with mental disorders, 124(30.7) stated that they cannot play with someone with mental illness. Conclusion: Adolescents had a negative attitude to mental illness, thus they and the community will require reorientation about the fact that mentally ill people are dangerous and violent. This can be done through health education and promotions, story telling, role plays, peer group activities